Educación ambiental para fomentar el reciclaje de aceite de cocina usado en hogares del centro poblado San Joaquin de Omaguas, Perú, 2021 - Flores Perea, Rosalvina (2024)
This research shows the results of the generation of alternative products, such as artisanal soap, as a product of the improvement in the management and use of used cooking oil. The generation of artisanal soaps is evaluated, with the aim of raising awareness among the population about the social and environmental management of used cooking oil and how to find a way to reuse it to reduce the pollution caused by dumping this oil waste into rivers and soils of your community. The sampling units were made up of 30 households divided into two groups, a control and experimental group from the Omaguas community of the “San Joaquín de Omaguas” Population Center, located on the banks of the Amazon River. From the training and the pre- and post-tests, very favorable results have been found, with a high rate of positive response from the participants in the experimental group, which has led to greater dissemination of the generation of soaps as recycling of the used cooking oil at the community level.